Asymptotic estimates for a nonlinear wave problem - Rojas Milla, Cristian; Pico Amaya, Alex (Revista MATUA, 2021)
We study the asymptotic solutions for a nonlinear damped wave problem showing the existence and uniqueness of solutions by contraction